2019
DOI: 10.1093/nar/gkz490
|View full text |Cite
|
Sign up to set email alerts
|

Diverse families of transposable elements affect the transcriptional regulation of stress-response genes in Drosophila melanogaster

Abstract: Although transposable elements are an important source of regulatory variation, their genome-wide contribution to the transcriptional regulation of stress-response genes has not been studied yet. Stress is a major aspect of natural selection in the wild, leading to changes in the transcriptional regulation of a variety of genes that are often triggered by one or a few transcription factors. In this work, we take advantage of the wealth of information available for Drosophila melanogaster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
61
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 81 publications
9
61
1
Order By: Relevance
“…A recent study performed using bioinformatic prediction coupled with Chip-seq data has revealed a significant enrichment of stress-related TFBSs in TEs [85], definitively supporting the idea that TEs are involved in stress responses.…”
Section: Tes As Promoter Suppliersmentioning
confidence: 66%
“…A recent study performed using bioinformatic prediction coupled with Chip-seq data has revealed a significant enrichment of stress-related TFBSs in TEs [85], definitively supporting the idea that TEs are involved in stress responses.…”
Section: Tes As Promoter Suppliersmentioning
confidence: 66%
“…Note that while no mortality after 9 h of malathion exposure was found for SE-Sto and RAL-375, 15% and 25% mortality was found for RAL-177 and iso-1, respectively. [33,49]. We checked whether any of the 17 TEs located nearby upregulated hub genes contained binding sites for cnc, the major transcription factor in xenobiotic and oxidative stress response [60].…”
Section: Resultsmentioning
confidence: 99%
“…regulation of signalling 20 (1) 48 (4) 38 (9) 7 (2) 10 (4) 38 (9) 31 (7) 3 (1) 54 (11) 31 (8) 27 ( 135 (1) 119 (1) 316 (2) 389 (2) 223 (1) 824 (1) -12 -4 0 enrichment score [33,49]. Note that four hub genes nearby TEs are present both in RAL-177 and in iso-1.…”
Section: (E) Half Of the Transposable Elements Located In Open Chromamentioning
confidence: 99%
“…For TFBS (Table 1), we used conSite website to screen all TFBS from insect in our sequences (Sandelin et al , 2004). To complete our analysis, we used the TFBS obtained from Villanueva-Cañas et al (2019) and we extracted PFM (position frequency matrix) of the 14 TFBS from the JASPAR2018 database (v.1.1.1) (Parcy et al , 2017). Then, we used TFBSTools (v.1.22.0) package from R software (v. 3.6.0) to convert in PWM (position weight matrix), and then search on the 6 lines and the reference genome of D. suzukii (Paris et al, 2020; R Core Team, 2019; Tan and Lenhard, 2016).…”
Section: Methodsmentioning
confidence: 99%